=S \: ( \: (bv)a \: )=(bv) \: Sa
S(a \otimes b)v=S \: ( \: (a \otimes b)v \=S \: ( \: (bv)a \: )=(bv) \: Sa
I am working on my homework for a class, and I am really stuck
the question I was given was:
prove that S(a ⊗ b) = (Sa) ⊗ b
Does anyone have any tips on how to solve this?
For further explanation this is problem 6a from this book on the page the link goes to
sorry I should have elaborated further. S is suppose to be a tensor map while a and b are supposed to be vectors
upon further looking at the book, it looks like a linear map. But I guess what they were just trying to get across is that it is a Tensor. such that v = Su. The hint in the back of the book says apply each side of the identity to an arbitrary vector v.